2021
DOI: 10.3389/fsoc.2021.669789
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Development of the Gender Embodiment of Enrichment: A Study of Gender Norms in Enrichment and Factors Related to Enrichment in a Sample of the Swedish Working Population

Abstract: Enrichment is a phenomenon described as the synergistic and beneficial effects of participating in both work and private life. Far too few studies have acknowledged the role of gender in enrichment. By applying a gender theoretical approach, this article has two aims; first, we aim to study the role of gender in enrichment by examining the factorial structure of enrichment in men and women; secondly, we aim to study the relationship between enrichment and work and private life factors in an approximately repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Regarding enrichment, Beham et al ( 2020 ) show that before the pandemic, women report higher levels of WLE. Hagqvist et al ( 2021 ), on the contrary, found no difference in the level of WLE between men and women but a higher level of LWE among women in the time before the pandemic. During the pandemic, many women experienced positive aspects of working from home, allowing them to create a closer relationship with family (Adisa et al, 2021 ; Hjálmsdóttir and Bjarnadóttir, 2021 ), which would suggest more enrichment.…”
Section: Introductionmentioning
confidence: 94%
“…Regarding enrichment, Beham et al ( 2020 ) show that before the pandemic, women report higher levels of WLE. Hagqvist et al ( 2021 ), on the contrary, found no difference in the level of WLE between men and women but a higher level of LWE among women in the time before the pandemic. During the pandemic, many women experienced positive aspects of working from home, allowing them to create a closer relationship with family (Adisa et al, 2021 ; Hjálmsdóttir and Bjarnadóttir, 2021 ), which would suggest more enrichment.…”
Section: Introductionmentioning
confidence: 94%